Anti-tumor effects of brucine immuno-nanoparticles on hepatocellular carcinoma - Qin JM; Yin PH; Li Q; Sa ZQ; Sheng X; Yang L; Huang T; Zhang M; Gao KP; Chen QH; Ma JW; Shen HB (International Journal of Nanomedicine, 2012)
Jian-Min Qin1, Pei-Hao Yin1, Qi Li1, Zhong-Qiu Sa1, Xia Sheng1, Lin Yang1, Tao Huang1, Min Zhang1, Ke-Pan Gao2, Qing-Hua Chen2, Jing-Wei Ma3, He-Bai Shen31Department of General Surgery, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, 2National Pharmaceutical Engineering Research Center; Shanghai Institute of Pharmaceutical Industry, 3Department of Physical Chemistry, Shanghai Normal University, Shanghai, People's Republic of ChinaBackground: Hepatocellular carcinoma is difficult to diagnose early, and most patients are already in the late stages of the disease when they are admitted to hospital. The total 5-year survival rate is less than 5%. Recent studies have showed that brucine has a good anti-tumor effect, but high toxicity, poor water solubility, short half-life, narrow therapeutic window, and a toxic dose that is close to the therapeutic dose, which all limit its clinical application. This study evaluated the effects of brucine immuno-nanoparticles (BIN) on hepatocellular carcinoma.Materials and methods: Anionic polymerization, chemical modification technology, and phacoemulsification technology were used to prepare a carboxylated polyethylene glycol-polylactic acid copolymer carrier material. Chemical coupling technology was utilized to develop anti-human AFP McAb-polyethylene glycol-polylactic acid copolymer BIN. The size, shape, zeta potential, drug loading, encapsulation efficiency, and release of these immune-nanoparticles were studied in vitro. The targeting, and growth, invasion, and metastasis inhibitory effects of this treatment on liver cancer SMMC-7721 cells were tested.Results: BIN were of uniform size with an average particle size of 249 ± 77 nm and zeta potential of -18.7 ± 4.19 mV. The encapsulation efficiency was 76.0% ± 2.3% and the drug load was 5.6% ± 0.2%. Complete uptake and even distribution around the liver cancer cell membrane were observed.Conclusion: BIN had even size distribution, was stable, and had a slow-releasing effect. BIN targeted the cell membrane of the liver cancer cell SMMC-7721 and significantly inhibited the growth, adhesion, invasion, and metastasis of SMMC-7721 cells. As a novel drug carrier system, BIN are a potentially promising targeting treatment for liver cancer.Keywords: cancer targeting, hepatocellular carcinoma, nanoparticles, targeted drug delivery, anti-tumor effect